Análise comparativa dos padrões neurodegenerativos da substância cinzenta em diferentes áreas corticais de ratos adultos submetidos à lesão isquêmica focal - SANTOS, Enio Maurício Nery dos (Universidade Federal do Pará, 2012)
Stroke can occur in any region of the central nervous system (CNS). The cerebral cortex is one of the most often affected areaby this acute neural disorder, but there are no studies that have compared the damaging pattern in different cortical regions after acomparable focal ischemia. The aim of this investigation was to evaluate the degenerative pattern of different cortical areas after focal ischemic injury. Focal ischemia was induced by stereotaxic microinjections of endothelin-1 (ET-1) into the somatosensory, motor and association cortices of adult rats (N = 45). The control animals were injected with the same volume of sterile saline (N = 27). The animals were perfused 1, 3 and 7 days after the ischemic event. The brain was removed, postfixed, cryoprotected, and sectioned in a cryostat. The general histopathology was evaluated in 50μm sections stained with cresyl violet. 20μm sections were submitted to immunohistochemistry for astrocytes (anti-GFAP), activated microglia / macrophages (anti-ED1) and overall microglial population (anti-Iba1). The damaging patterns werequalitatively evaluated under optical microscopy and quantitatively by counting the number of cells in the ipsilateral and contralateral sides to injury.Descriptive statistics and comparisons within and between groups were performed using analysis of variance with Tukey post-hoc test. Conspicuous ischemic tissue loss, microglial activation and astrocytosis were observed mainly 3 and 7 days after ischemia, which was not observed in control animals. The tissue loss and activation of glial cells were more intense in the somatosensory cortex, followed by the motor cortex. The association cortex displayed less damage compared to other cortical areas, which was confirmed by quantitative analysis. The results suggest that an ischemic lesion of the same intensity induces a differential pattern of tissue loss and neuroinflammation, depending on the cortical area, and that the primary sensory and motor areas are more susceptible to ischemia than association areas.